Urgensi Pembentukan Undang-Undang Kemitraan Untuk Pengemudi Ojek Online - Aryaputri, Aqila Shafiqa; Mufti, Muhammad Wildan; Siregar, Tiara Rebecca Kezia; Maulana, Muhammad Irfan (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Technological advancements have transformed the transportation sector with the emergence of online motorcycle taxi services, such as PT Gojek, significantly impacting Indonesia's digital economy. However, the legal status of online motorcycle taxi drivers, deemed